THE USE OF INTERNET AND SOCIAL MEDIA FOR DRUG INFORMATION SERVICES IN PHARMACIES IN YOGYAKARTA PROVINCE: A STUDY OF ASTHMA CARE - Fajar Ira Juwita; Aris Widayati; Enade Perdana Istyastono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2020)
Industrial revolution 4.0 is the process of digitizing the industry that leds health services in the era of application of Information and Communication Technology (ICT) called e-health. The application of ICT in Pharmacy is known as e-pharmacy. The role of pharmacists in Drug Information Services by utilizing ICTs has an effect on e-health literacy which ultimately supports the success of patient therapy. This is very important for patients with chronic diseases who are receiving treatment for a long time, one of which is asthma patients. Therefore, this study aims to explore pharmacist perceptions regarding the use of the internet and social media for drug information services, with a case study of services in asthma patients. This research is descriptive with a qualitative approach. Data is collected by interviews using an interview guide that has been validated in a professional judgment. Interviews were conducted with pharmacist participants who provided pharmacy services to asthma patients, who were selected purposively in March to July 2019. Data from interviews were transcribed verbatim, then a thematic analysis was performed. Ethical clearance has been obtained under number 945/ C.16/ FK/ 2019. The results of the study mention the use of the internet and social media indicate the potential capabilities of pharmacists in health services and also the challenges of transformation to the role of pharmacists in the e-pharmacy era. This study also mentions the urgency of establishing regulations regarding e-pharmacy that is driven by the violation from the internet and social media use. Improvement of ICT infrastructure in the pharmacy field as well as the pharmacist's contribution on the provision of drug information for chronic diseases, including asthma, are urgently required.